IDENTIFICATION OF ACTORS AND MARKETING MARGINS OF PROTECTED FRESHWATER STINGRAYS IN MUSI RIVER, SOUTH SUMATERA - Azzahra, Sahaya Aulia; Wijayanti, Pini; Septiani, Nabila Nur; Nikmah, Lailatun (Bogor Agricultural University, 2025)
The Musi River in Palembang, South Sumatra-Indonesia, serves as the habitat for three protected freshwater stingray species: the marbled whipray (Fluvitrygon oxyrhynchus), the white-edge whipray (Fluvitrygon signifier), and the giant freshwater whipray (Urogymnus polylepis). All three species are categorized as endangered on the IUCN Red List and are listed under Appendix II of CITES. However, communities along the Musi River continue to trade freshwater stingrays freely in local markets. This research aims to identify the economic potential of the freshwater stingray trade, which is suspected to drive illegal capture, by analyzing its supply chain and estimating its marketing margins. Descriptive analysis and marketing margin analysis were employed to address the research objectives. The findings indicate that the freshwater stingray trade in the Musi River involves a short supply chain and covers a wide range of capture areas. Positive marketing margins ranging from IDR 17,000 to IDR 60,000 per kilogram for the white-edge whipray and the giant freshwater whipray, and up to IDR 200,000 per individual for the marbled whipray, provide empirical evidence that freshwater stingrays contribute to the income of the market actors, thereby potentially encouraging the trade of protected species and potentially driving illegal trade. Keywords: Conservation, illegal trade, ornamental fish, protected species, wildlife trafficking